Development of Online Coaching Model to Improve Entrepreneurial Skills and Start-up Business Management - Rustiadi, Sonny; Nurulfiqri, Zartikazahra (Yayasan Pendidikan Belajar Berdikari, 2024)
This study aims to analyze the influence of coaching methods, coaching technology, interaction between coaches and participants, and material personalization on entrepreneurial skills. This study uses a quantitative approach with multiple linear regression method. Data were collected from 100 respondents who participated in the entrepreneurial coaching program. Data were analyzed using t-test (partial effect), F-test (simultaneous effect), and coefficient of determination to assess the quality of the model. The results showed that partially, coaching technology and material personalization had a significant effect on entrepreneurial skills, while coaching methods and interaction between coaches and participants did not have a significant effect. Simultaneously, the four independent variables had a significant influence on entrepreneurial skills with a model contribution of 40.6%. The findings emphasize the importance of innovation in entrepreneurial coaching, especially through the use of technology and personalization of materials to be more effective in improving entrepreneurial skills. This research contributes to the development of a more adaptive and technology-based coaching model in improving entrepreneurial skills